2014
DOI: 10.3389/fnhum.2014.00334
|View full text |Cite
|
Sign up to set email alerts
|

Accurate expectancies diminish perceptual distraction during visual search

Abstract: The load theory of visual attention proposes that efficient selective perceptual processing of task-relevant information during search is determined automatically by the perceptual demands of the display. If the perceptual demands required to process task-relevant information are not enough to consume all available capacity, then the remaining capacity automatically and exhaustively “spills-over” to task-irrelevant information. The spill-over of perceptual processing capacity increases the likelihood that task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 97 publications
4
11
2
Order By: Relevance
“…Interestingly, we did not observe enhanced alpha suppression over visual areas in preparation for a high visual load. In accordance with findings of Sy et al 5 , if a low task load was expected, attentional capacity might have been used for deeper cue processing (and possible integration of modalities). Yet this is not what was observed and we cannot draw any conclusions based on our data.…”
Section: Ldap By Hopf and Mangunsupporting
confidence: 83%
See 2 more Smart Citations
“…Interestingly, we did not observe enhanced alpha suppression over visual areas in preparation for a high visual load. In accordance with findings of Sy et al 5 , if a low task load was expected, attentional capacity might have been used for deeper cue processing (and possible integration of modalities). Yet this is not what was observed and we cannot draw any conclusions based on our data.…”
Section: Ldap By Hopf and Mangunsupporting
confidence: 83%
“…However, it remains to be elucidated whether top-down factors, such as expectation of perceptual load, can already attenuate the task-irrelevant areas prior to the onset of the stimuli. While cueing / manipulation of sensory perceptual load has been found to modulate post-target attentional resource allocation 4,1,5,6 , the pre-stimulus neural allocation of resources in anticipation of visual load has rarely been studied. Here we investigated how expectation about perceptual task load in the visual domain, influenced preparatory activity in task-relevant and irrelevant sensory cortices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is theorized that when the distractor and target are part of the same object, paying more attention to the target means paying more attention to the distractor. Expectancy, as manipulated through precueing targets and running blocks of all high-load or all low-load trials, has also been shown to reduce or eliminate distractor interference in low-load conditions (Johnson, McGrath, & McNeil, 2002;Sy, Guerin, Stegman, & Giesbrecht, 2014;Theeuwes, Kramer, & Belopolsky, 2004). Yet many other studies have presented blocks of either high-or low-load trials, in which load could be accurately predicted, and have still produced evidence in support of load theory (Beck & Lavie, 2005;Forster & Lavie, 2007bKonstantinou & Lavie, 2013) Experiments that manipulate perceptual and cognitive load simultaneously (so called "sandwich tasks" like the one shown in Fig.…”
Section: Other Criticismsmentioning
confidence: 99%
“…For example, physically salient distracters can fail to capture attention when presented outside the current focus of attention (Belopolsky, Zwaan, Theeuwes, & Kramer, 2007) and, under some conditions, when presented at completely task-irrelevant locations (Johnson, McGrath, & McNeil, 2002;Sy, Guerin, Stegman, & Giesbrecht, 2014). There is evidence of a similar effect with value-driven capture.…”
Section: Value-driven Capturementioning
confidence: 99%